Overview of State Assist Program (Tufts Archival Research Center, 2007)
Marginalia; Overview of state American Stop Smoking Intervention Study for Cancer Prevention (ASSIST) programs. Discusses progress and issues in each state and government funding. Indentifies ASSIST objectives. Provides history of ASSIST. Summarizes activities and plans in a timeline. Discusses national coordination and possible encouragement to the lobby. Lists state participants.